MOTIF DAN POLA PENGGUNAAN MEDIA SOSIAL INSTAGRAM DI KALANGAN MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIMED - Muhammad Fachri Syahreza; Irwan Syari Tanjung (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
ABSTRACT This research was conducted to obtain motives and the usage patterns instagram among the students unimed the economics faculty of economic education course of study. Population in this research is 490 people. Sample a total of 49 people in this research. A theory that used in this research is a theory uses and gratification. Methods used in this research is quantitative research methods. The technique of analysis in this research is a technique of the data analysis by doing tabulation of the results of such data that has been filled by respondents, the data obtained next shown in the form table a frequency distribution. The result of this research revealed that motive respondents using instagram is to “pleasure seeking/ entertainment“ Using patterns of instagram in respondents tend to irregular, according to the research using patterns of instagram generally seen from the frequency of a total of more than 4 ( four ), duration less than 1 ( one ) hours, the use of more at night, content most widely seen is a photo sites tutorial video. Keyword: Motives, Patterns and Instagram